Hierarchical Structure of Magnetic Nanoparticles -Fe3O4- Ferrofluids Revealed by Small Angle X-Ray Scattering - Gea Fitria; Arum Patriati; Mujamilah Mujamilah; Maria Christina Prihatiningsih; Edy Giri Rachman Putra; Siriwat Soontaranon (Universitas Gadjah Mada, 2021)
Small-angle X-ray scattering (SAXS) experiments were set up to investigate the form and structure of Fe3O4 magnetic nanoparticles (MNPs) using BL1.3:SAXS at the Synchrotron Light Research Institute (SLRI) of Thailand in the range of scattering vector q, 0.7 < q (nm–1) < 4. The scattering data from samples, background, and empty cells were collected and then subtracted using small-angle X-ray scattering image tool (SAXSIT) software. The analysis of the corrected scattering patterns for four different pH, i.e., 2, 3, 4, and 5, has been revealed by applying log-normal spherical and mass fractal models calculation. The results showed that the SAXS measurement could investigate the hierarchical structures of MNPs Fe3O4 containing primary and secondary particles. The two-dimensional fractal (Df) aggregates as secondary particles (in volume) have various sizes ranging from 21 to 103 nm in diameter, confirming the correlation to their pH. Those structures consist of primary particles with a mean length of 2 nm in radius and the particle size distribution (σ) of 0.5.